Implementación de una aplicación móvil para la visualización de la producción científica de la Universidad Técnica de Cotopaxi. - Aispur Calvopiña, Edison Israel (2018)
The purpose of this study was to develop a computer system for the scientific production visualization at “Universidad Técnica de Cotopaxi”; the software implemented is a mobile application that is responsible for making an inventory of everything that covers scientific production; it means, books, scientific papers published in indexed scientific journals and seminars conducted by teachers of each career at “Universidad Técnica de Cotopaxi”. The Android Studio tool was used in order to develop the application, with the Android interface code of high technology, the source code is encoded in the PHP programming language, the database management system for the information storage is developed in MySQL. The methodology used in the development of the system is the Mobile-D agile approach in each of the stages determined by it. The Mobile application allows visualizing the scientific production that is carried out by teachers at “Universidad Técnica de Cotopaxi”. Therefore, the development of the mobile application will help both teachers and external users of the University, that is why the mobile application was designed to free access, so that they can be interested in the content covered by the mobile application which is clear and mutually linked to the website of research.